Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1128/aem.02989-12
|View full text |Cite
|
Sign up to set email alerts
|

Gene Identification and Substrate Regulation Provide Insights into Sulfur Accumulation during Bioleaching with the Psychrotolerant Acidophile Acidithiobacillus ferrivorans

Abstract: The psychrotolerant acidophile Acidithiobacillus ferrivorans has been identified from cold environments and has been shown to use ferrous iron and inorganic sulfur compounds as its energy sources. A bioinformatic evaluation presented in this study suggested that Acidithiobacillus ferrivorans utilized a ferrous iron oxidation pathway similar to that of the related species Acidithiobacillus ferrooxidans. However, the inorganic sulfur oxidation pathway was less clear, since the Acidithiobacillus ferrivorans genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 36 publications
1
35
0
1
Order By: Relevance
“…6). is likely, especially in oxic-anoxic transition zones and the majority of the lake water where temperature and sulfate concentrations predict significantly decreased oxygen concentrations compared to atmospheric levels (Liljeqvist et al, 2013). Chemosynthetic primary production is likely driven by the (micro)aerobic oxidation of reduced iron and sulfur minerals by members of the Firmicutes and Actinobacteria phyla, the cproteobacterium Acidithiobacillus spp., and Archaea in the Sulfolobaceae family.…”
Section: Biogeochemical Model Of Bsl Ecosystemmentioning
confidence: 99%
See 1 more Smart Citation
“…6). is likely, especially in oxic-anoxic transition zones and the majority of the lake water where temperature and sulfate concentrations predict significantly decreased oxygen concentrations compared to atmospheric levels (Liljeqvist et al, 2013). Chemosynthetic primary production is likely driven by the (micro)aerobic oxidation of reduced iron and sulfur minerals by members of the Firmicutes and Actinobacteria phyla, the cproteobacterium Acidithiobacillus spp., and Archaea in the Sulfolobaceae family.…”
Section: Biogeochemical Model Of Bsl Ecosystemmentioning
confidence: 99%
“…Additionally, hydrogen-mediated primary production via Hydrogenobaculum spp. is likely, especially in oxic-anoxic transition zones and the majority of the lake water where temperature and sulfate concentrations predict significantly decreased oxygen concentrations compared to atmospheric levels (Liljeqvist et al, 2013). Carboxydotrophy also seems to play a role in organic synthesis in this ecosystem, although the identity of the carboxydotrophs is 6 Model of Boiling Springs Lake biogeochemistry.…”
Section: Biogeochemical Model Of Bsl Ecosystemmentioning
confidence: 99%
“…Two At. ferrivorans strains have been genome sequenced (Liljeqvist et al 2011; Talla et al 2013) and potential genes involved in iron and ISC oxidation have been identified (Liljeqvist et al 2013). Transcriptomes analyses were used to identify the expression of At.…”
Section: Introductionmentioning
confidence: 99%
“…The A. ferrivorans SS3 genome contains two additional copies of the rus gene (Liljeqvist et al ., ) and its three Rus proteins not only have a high Blastp score (>85%) to Rus from A. ferrooxidans but all of them also conserve the same copper‐binding site. RusA from A. ferrivorans SS3 is the protein with the highest identity compared with Rus from A. ferroxidans and it forms part of the rus operon from A. ferrivorans together with the gene coding for the AcoP protein (Liljeqvist et al ., ).…”
Section: Copper Resistance Of Biomining Bacteriamentioning
confidence: 99%
“…The A. ferrivorans SS3 genome contains two additional copies of the rus gene (Liljeqvist et al ., ) and its three Rus proteins not only have a high Blastp score (>85%) to Rus from A. ferrooxidans but all of them also conserve the same copper‐binding site. RusA from A. ferrivorans SS3 is the protein with the highest identity compared with Rus from A. ferroxidans and it forms part of the rus operon from A. ferrivorans together with the gene coding for the AcoP protein (Liljeqvist et al ., ). In the light of the recent report suggesting that Rus and AcoP are copper resistance determinants in A. ferrooxidans ATCC 23270 (Navarro et al ., ), it will be of interest to study whether these proteins have a similar role in copper resistance in A. ferrivorans .…”
Section: Copper Resistance Of Biomining Bacteriamentioning
confidence: 99%